(untitled) (Research, Society and Development, 2022)
The search for materials with lower environmental impact is a fundamental agenda for a constant evolution of civil construction and society, becoming increasingly recurrent. These materials have to present a reduction in the atmosphere pollutants emission, fulfill the technical requirements established by the standards according to the purpose of each composition, enable to reduce or reuse of waste, and a good cost-benefit ratio. Thus, this article aims to analyze the economic and environmental viability of the soil-cement brick in civil construction in Brazil, as well as to identify the main results of the incorporation of waste in its manufacture. This is an integrative bibliographic review of the literature, which was carried out between August 2021 and January 2022. The soil-cement brick has an economy of 41% when compared to ceramic brick, and can be articulated with the social interest housing; in addition, it generates less environmental impact, either by reducing polluting gases - a 29.5% reduction in CO2, or by reusing waste. It is possible to find in the literature the incorporation of several residues with different results. Therefore, the potential of the soil-cement brick is evident by the reuse of waste, helping in the disposal and reuse; for having a lower financial cost in the construction and lower CO2 emission; in addition to having the potential to be used in housing programs in order to reduce the housing deficit in Brazil. However, more research is needed with this constructive method, in order to acquire greater reliability of this material.